Profil Afektif Siswa dalam Pendekatan Pembelajaran phi-log Berwawasan Karakter Bangsa - Suyana, Iyon (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Demands of the 2013’s curriculum that applied in Indonesia developed so that existing learning patterns into a learning-centered interactive learners, active-looking, based multimedia tools, and critical. The curriculum was developed on the basis of the awareness that science and technology is developing dynamically. Web Based Learning is learning in accordance with the expected learning patterns. This study uses a "one-group time series design" is a treatment that is performed several stages without a comparison group. The study population was 15 students junior high / high school year 2014/2015 is chosen randomly. Data obtained by the tests mastery of concepts, questionnaires affection, and the observation sheet character assessment. While processing the data for affective and characters using qualitative analysis quantified in percentage form profile. Affective aspects of the dominant profile after use "π-based log PBL" is an aspect of honesty and motivation, with a percentage respectively 87.29% and 84.79% with very good category. As for the aspect of curiosity, positive attitude and confidence respectively 77.7%, 73.95% and 69.58% were third into either category. It can be concluded that the use of "π-based log PBL" in learning can build honesty and motivation very well and build curiosity, positive attitude and confidence well. Keyword: positive attitude, phi-log .